FHL2 Regulates Natural Killer Cell Development and Activation during Streptococcus pneumoniae Infection - Baranek, Thomas; Morello, Eric; Valayer, Alexandre; Aimar, Rose-France; Bréa, Déborah; Henry, Clemence; Besnard, Anne-Gaelle; Dalloneau, Emilie; Guillon, Antoine; Dequin, Pierre-François; Narni-Mancinelli, Emilie; Vivier, Eric; et al. (Frontiers in Immunology, 2017)
Recent in silico studies suggested that the transcription co-factor LIM-only protein FHL2 is a major transcriptional regulator of mouse NK cells. However, the expression and role of FHL2 in NK cell biology are unknown. Here, we confirm that FHL2 is expressed in both mouse and human NK cells. Using FHL2-/- mice, we found that FHL2 controls NK cell development in the bone marrow and maturation in the peripheral organs. To evaluate the importance of FHL2 in NK cell activation, FHL2-/- mice were infected with Streptococcus pneumoniae. FHL2-/- mice are highly susceptible to this infection. The activation of lung NK cells is altered in FHL2-/- mice, leading to decreased IFNg production and a loss of control of bacterial burden. Collectively, our data reveal that FHL2 is a new transcription co-factor implicated in NK cell development and activation during pulmonary bacterial infection.